Techniques used in teaching grammar among TESL trainee teachers / Nurul Salwanie Sapari - Sapari, Nurul Salwanie (2011)
The concern of this research is to find out the most frequent technique used by TESL Trainee Teachers in teaching grammar based on their personal experience in schools, it was also conducted in order to see the factors underlying the technique chosen as well as the problems encountered by trainee teachers from planning stages until executing stages. Finally, the steps taken in order to overcome the problems as well as the recommendations for the future TESL Trainee Teachers were also collected through these two instruments. A total of twenty TESL Trainee Teachers who are currently pursuing their final semester participated in this study. The questionnaires were distributed to these twenty participants and each of the participants was interviewed by the researcher in order to find the answer for the research questions, in brief, the use of inductive approach in planning the lessons to teach grammar has been seen as the most reliable and popular method to be used in the classroom teaching, some problems were identified from the initial stage until the executing stages such as; the suitability of the contents to be taught according to the students' level. Several recommendations were found in order to overcome this problem as mentioned in this academic exercise.